Analytical method Development and validation of Ivabradine by using RP-HPLC - Dr. Sachin N. Kapse,; Ms. Sayami V. Shirsath,; Mr. Roshan D. Patil,; Mr. Shekhar C. Shinde,; Mr. Rahul N. Patil,; Dr. Rameshwar S. Rathod,; Mr. Yogesh S. Wankhede, (The Bioscan, 2025)
The RP-HPLC method, which makes use of an XTERR C8 column (150mm × 4.6mm, 3.5μm) and a mobile phase of acetonitrile:0.01N KH2PO4(60:40) of HPLC grade, became created and accepted to be used in Ivabradine analysis. Buffer's pH became stored at 3. After being subjected to a 10-minute sonication, the use of a 0.45μm Nylon clear out, A 0.9mL/min waft charge became used to clear out the cellular section. After 260 nm of detection, it became observed that Ivabradine had a 1.846-minute retention period. Linearity became found with equation y=14200x+106895, from 80–120 μg/mL (R2 became the coefficient of determination). ICH hints had been accompanied with inside the validation of the approach.